Wavefront sensing at X‐ray free‐electron lasers. (20th June 2019) - Seaberg, Matthew; Cojocaru, Ruxandra; Berujon, Sebastien; Ziegler, Eric; Jaggi, Andreas; Krempasky, Juraj; Seiboth, Frank; Aquila, Andrew; Liu, Yanwei; Sakdinawat, Anne; Lee, Hae Ja; Flechsig, Uwe; et al.
Abstract : Here a direct comparison is made between various X‐ray wavefront sensing methods with application to optics alignment and focus characterization at X‐ray free‐electron lasers. Difference wavefront measurements with and without a corrective phase plate agreed with its design to within λ/20, enabling a direct quantitative comparison between methods. Abstract : Here a direct comparison is made between various X‐ray wavefront sensing methods with application to optics alignment and focus characterization at X‐ray free‐electron lasers (XFELs). Focus optimization at XFEL beamlines presents unique challenges due to high peak powers as well as beam pointing instability, meaning that techniques capable of single‐shot measurement and that probe the wavefront at an out‐of‐focus location are desirable. The techniques chosen for the comparison include single‐phase‐grating Talbot interferometry (shearing interferometry), dual‐grating Talbot interferometry (moiré deflectometry) and speckle tracking. All three methods were implemented during a single beam time at the Linac Coherent Light Source, at the X‐ray Pump Probe beamline, in order to make a direct comparison. Each method was used to characterize the wavefront resulting from a stack of beryllium compound refractive lenses followed by a corrective phase plate. In addition, difference wavefront measurements with and without the phase plate agreed with its design to within λ/20, which enabled a direct quantitative comparison between methods. Finally, a path toward automated alignment at XFEL beamlines using a wavefront sensor to close the loop is presented.